The New Anti-Terrorism Act of the Philippines and Its Conflict with the International Human Rights System - Nader Naseri Naseri Pilehdaraq; Hooriyeh Hosseini Akbarnezhad (پژوهشهای حقوقی)
Terrorism has always been a threat to the lives and security of the Filipino people. The existence of various terrorist threats in this country inevitably necessitated a codified mechanism to deal with terrorist threats. The country's 2007 Human Security Act was enacted to combat terrorism and was intended to combat militants in the southern Philippines. Critics of the law argue that the amendment was necessary to pave the way for the prosecution and punishment of perpetrators of terrorism, which led to the passage of the 2020 Anti-Terrorism Law. Compliance with the Philippine Constitution is currently being challenged by various domestic and foreign groups and has been reviewed by the Supreme Court. But the government, and especially the president himself, was determined to pass the law quickly and did not show any leniency. Some Philippine government officials believe that the review of this law shows that there is a guarantee of compliance with human rights standards in its place and this in itself can be considered a strong reason for the law to comply with international human rights instruments. But a careful examination of the law can ultimately lead the analyst to the conclusion that, despite the lawmakers' consideration of compliance with human rights standards, which appear to have been largely successful, the issue of long-term detention can be considered a flaw for it.